Desarrollo de la metodología de diseño de cimentaciones para torres de interconexión eléctrica en zonas lacustres, aluviales, costeras y de montaña en el territorio colombiano (2019)
This document consists of the presentation of the existing methodologies for the analysis of foundations for self-supporting electrical interconnection (transmission) towers. Based on these establish an economic method for the development of this type of analysis. The importance lies in the difference with the traditional analyzes given the presence of traction in the foundation and in the explorations carried out at present, since there is no appropriate protocol that integrates these and the existing regulations in Colombia for soil analysis are the NSR -10 in its title H and the Technical Regulation of the Potable Water and Basic Sanitation Sector –RAS in title G, without these considering these types of structures.